Importance of moral reasoning in drug abuse - Erk, Mehmet Aykut; Fırat, Sunay (Journal of Dependence, 2018)
Risky behavior such as substance use and how it affects from one’s moral development and ethical values have always been a critical discussion point in literature. Psychoactive or narcotic drug usage mostly has been considered as a public health problem or a security problem for individuals. This paper aims to examine the importance of moral reasoning in drug abuse. The goal is to contribute the psychoactive and narcotic drug abusers’ rehabilitation (individual rehabilitation and treatments) and social integration process by creating a new perspective including how adolescents’ and young adults’ drug abuse affects from their moral developments and how moral theories explain aforesaid problem by examination of literature. According to literature it has been thought which there a high connection between individuals’ moral is reasoning development and risky behaviors such as substance abuse, antisocial behaviors etc. While risky behaviors affect individual directly they have been accepted as a personal preference, choices which affects environment or community have been accepted as moral behaviors. To sum up it should not be forgotten that in order to execute a successful treatment and rehabilitation process the resource which in need lays inside the individual.